2023
DOI: 10.1002/adbi.202200292
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Disruption in Night Shift Work and Its Association with Chronic Pulmonary Diseases

Abstract: Globalization and the expansion of essential services over continuous 24 h cycles have necessitated the adaptation of the human workforce to shift‐based schedules. Night shift work (NSW) causes a state of desynchrony between the internal circadian machinery and external environmental cues, which can impact inflammatory and metabolic pathways. The discovery of clock genes in the lung has shed light on potential mechanisms of circadian misalignment in chronic pulmonary disease. Here, the current knowledge of cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 119 publications
1
3
0
Order By: Relevance
“…In addition, shift work, especially night shift work, was shown to be associated with a higher risk of chronic physical disorders, including diabetes, cardiovascular disease, and cancer [1,40]. Consistent with the findings of previous studies [41][42][43], current results also suggested that shift work was significantly associated with an increased risk of poor health outcomes among the general population in China.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, shift work, especially night shift work, was shown to be associated with a higher risk of chronic physical disorders, including diabetes, cardiovascular disease, and cancer [1,40]. Consistent with the findings of previous studies [41][42][43], current results also suggested that shift work was significantly associated with an increased risk of poor health outcomes among the general population in China.…”
Section: Discussionsupporting
confidence: 90%
“…There are several potential mechanisms underlying the associations between night shift work and COPD risk. Night shifts may trigger circadian disruption, resulting from the mismatch between internal circadian rhythms and external environmental conditions [40]. Subsequently, the changes in sleep-wake cycles and exposure to light-dark patterns can lead to abnormal levels of cortisol, melatonin, and body temperature, which have been associated with COPD [40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Night shifts may trigger circadian disruption, resulting from the mismatch between internal circadian rhythms and external environmental conditions [40]. Subsequently, the changes in sleep-wake cycles and exposure to light-dark patterns can lead to abnormal levels of cortisol, melatonin, and body temperature, which have been associated with COPD [40][41][42][43]. For example, the night shift can alter the circadian rhythm, which has been reported to suppress melatonin biosynthesis [15,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Altered production of some reactive species had been observed at an early stage of the pandemic, often accompanied by alterations in the duration and quality of sleep, and mood changes. Yet, manifestations of the latter were also seen in uninfected healthcare personnel working night shifts [ 5 ], and in the population at large due to the unprecedented scope and scale of the societal restrictions [ 6 ]. Moreover, circadian disruptions had been observed before the pandemic in patients suffering from chronic pulmonary disease and other metabolic diseases such as diabetes and obesity [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%